Determinants of economic performance of micro-credit clients and prospect of Islamic microfinance in Malaysia - Md Saad, Norma; Duasa, Jarita (International Shari'ah Research Academy for Islamic Finance (ISRA), 2010)
This study is divided into two parts. The first part of the study utilises econometric models to assess the economic performance of clients participating in the microcredit programme of Amanah Ikhtiar Malaysia (AIM). Several proxies are used for the economic performance variable (dependent variable), including level of earnings/income, ratio of spending to income and value of assets. The regressors (independent variables) used are education level, age, amount of loan, source of income and ownership of assets. The second part of this study concentrates on analysing the prospects of introducing Islamic microfinance products to be used in microfinance activities in Malaysia. In the first part of the study, we find that the economic performance of AIM participants is significantly determined by the amount of money borrowed from AIM. Other factors found to influence the respondents’ economic performance are education level, age, gender, assets owned before joining AIM and area of residence. Because level of education is found to contribute significantly to the economic performance of AIM participants, it is suggested that AIM work to educate its borrowers, and more specifically, to provide business training. In the second part of the study, the results show that there is a great demand for Islamic microfinance products in Malaysia. The findings of the study could serve as general guidelines for microfinance institutions in designing Islamic microfinance products for either Muslims or non-Muslim micro- entrepreneurs.